Urinary Uric Acid and Creatinine Ratio as a Marker of Perinatal Asphyxia - Kartika Gulati; Shree Vishnoi; Sandeep Choudhary; Rakesh Jora (Mashhad University of Medical Sciences, 2022)
Background: Prediction of the outcome of perinatal asphyxia (PA) is important but formidable. Apgar score has a limited role in predicting the outcome. Urinary uric acid and creatinine ratio (UA/Cr) is an early, noninvasive, and cheap biomarker of PA which may predict its morbidity. This study aimed to determine the urinary UA/Cr in neonates with PA, compare it with UA/Cr in non-asphyxiated neonates, and derive the optimum cut-off value of this ratio to label PA.Methods: This observational cross-sectional study was carried out on 100 term neonates appropriate for gestational age (AGA) with PA (cases) and 100 non-asphyxiated term AGA babies (controls). Urine samples were collected within 24 h of life; moreover, uric acid and creatinine levels were determined by an auto-analyzer.Results: The mean urinary UA/Cr ratio was significantly higher in the cases, compared to the controls (3.41±0.68 vs. 1.99±0.23) (P<0.0001). The cut-off value of this ratio to label PA was>2.5 with sensitivity, specificity, positive predictive value, and negative predictive value of 98%. Urinary UA/Cr ratio and cord blood pH were significantly correlated with each other (correlation coefficient r=-0.8951, P<0.001). Moreover, the urinary UA/Cr ratio and 5-min Apgar score were also significantly correlated with each other (r=-0.8806, P<0.001).Conclusion: Urinary UA/Cr ratio is a non-invasive, cheap, and reliable marker for PA with good predictive value in this study.